Who Can Support the Introduction of Self-Driving Military Vehicles? - Szikora, Péter (Honvédségi Szemle – Hungarian Defence Review, 2025)
The aim of the current paper is to map attitudes towards self-driving vehicles along eight key questions, which look at the challenges of the technology, risk perception, and potential civil and military uses. The results show that trust in the cybersecurity of self-driving cars is strongly correlated with fear of new technologies, privacy concerns, and fear of failure. Respondents with confidence towards self-driving technology are more open to military applications, while those without confidence have higher concerns about controllability. The cluster analysis identified three distinct clusters of attitudes: negative perceptions, cautiously open, and technology-friendly. The results highlight the diversity of trust patterns and contribute to a better understanding of the social acceptance of autonomous vehicles.